2014
DOI: 10.1186/s12935-014-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of undifferentiated embryonic cell transcription factor-1 (UTF1) in breast cancers and their matched normal tissues

Abstract: ObjectivesUndifferentiated embryonic cell transcription factor-1 (UTF1) plays a critical role in the developmental timing during embryonic development. However, there is little paper dealing with UTF1 expressed in adult tissues. In the present study, we evaluate the expression of UTF1 in breast cancer and its correlation with clinicopathological parameters.MethodsReal-time polymerase chain reaction (real-time PCR) was applied to detect the expression of UTF1 mRNA in the 55 pairs of samples of breast cancer tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…In this study, we found that the poor prognosis of breast cancer and the malignant biological characteristics of breast cancer cells were correlated with the high expression of UTF1, which plays a role as an oncogenic factor in breast cancer. However, this is in contrast to the results reported previously, which suggested that UTF1 expression is down-regulated in breast cancer and that UTF1 functions as a protective factor in breast tissue ( 16 ). It is worth noting that this paradox is also present in cervical cancer ( 11 , 17 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we found that the poor prognosis of breast cancer and the malignant biological characteristics of breast cancer cells were correlated with the high expression of UTF1, which plays a role as an oncogenic factor in breast cancer. However, this is in contrast to the results reported previously, which suggested that UTF1 expression is down-regulated in breast cancer and that UTF1 functions as a protective factor in breast tissue ( 16 ). It is worth noting that this paradox is also present in cervical cancer ( 11 , 17 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although differences in the gene expression and methylation signatures of the TME are associated with significant prognostic differences in patients with STSs 12 , such differences in the TME are unlikely to explain the results in our remainder samples, as most of our cases (10 of 14 paired cases) were over-represented by so-called 'cold tumours' , devoid of TILs. On the other hand, the role of UTF1 (undifferentiated embryonic cell transcription factor 1), which plays a role in stem-cell development 69 and carcinogenesis [70][71][72] , and NTRK3 in RMS has not been described. NTRK3 methylation has been reported in other tumours 73 and although tyrosine kinase inhibitors are widely available for NTRK-translocated tumours, the effect of these TRK inhibitors has not been explored in tumours with NTRK gain or loss due to methylation.…”
Section: Discussionmentioning
confidence: 99%